Evaluating Potential of Online Sales by "Electronic Shopping Test": A Conceptual Framework - Haque, Ahasanul; Sadeqzadeh, Javed; Khatibi, Ali (Indian Journal of Marketing, 2007)
Companies look at online sales as an experience rather than an investment. They still confuse how many consumers are ready to buy online. In addition, products have different acceptance level among customers and not all products can be sold at web stores. ES Test is a simple three steps approach to determine potential of online sales. By ES Test, consumer attitude towards online shopping, familiarity and confidence, and product characteristics are evaluated and overall ES Test is measured. Any score higher than 20 shows suitability for online sales. This study tried to establish relationship between potential of online sales mainly with three factors. Results showed that there is significant relationship between potential of online sales and consumer attitude towards online shopping, product characteristics, and familiarity and confidence. Evaluating of selling Malaysian Airline ticket by ES Test indicated that Malaysian Airline ticket is a suitable product for selling online in Malaysia.